2007
DOI: 10.1111/j.1467-9353.2006.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Regional Economic Growth in the U.S. Midwest

Abstract: In this paper we examine some of the economic forces that underlie economic growth at the county level. In an effort to describe a much more comprehensive regional economic growth model, we address a variety of different growth hypotheses by introducing a large number of growth related variables. When formulating our hypotheses and specifying our growth model we make liberal use of GIS (geographical information systems) mapping software to "paint" a picture of where growth spots exist. Our empirical estimation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 25 publications
(12 reference statements)
0
24
0
Order By: Relevance
“…Cheshire and Sheppard 1995, Giannias, 1998, Shultz and King 2001, or both wage and rent differentials (Roback, 1982, Kahn, 1995, Berger et al, 2003. A number of recent studies link the analysis of quality of life to other fields, such as urban competitiveness and growth (Deller et al, 2001, Monchuk et al, 2007, Wu and Gopinath, 2008, migration (Douglas and Wall, 2000), and environmental quality (Brasington andHite, 2005, Redfearn, 2009). …”
mentioning
confidence: 99%
“…Cheshire and Sheppard 1995, Giannias, 1998, Shultz and King 2001, or both wage and rent differentials (Roback, 1982, Kahn, 1995, Berger et al, 2003. A number of recent studies link the analysis of quality of life to other fields, such as urban competitiveness and growth (Deller et al, 2001, Monchuk et al, 2007, Wu and Gopinath, 2008, migration (Douglas and Wall, 2000), and environmental quality (Brasington andHite, 2005, Redfearn, 2009). …”
mentioning
confidence: 99%
“…This typically occurs when households relocate across different labor markets. The corresponding empirical 2 The improvement in natural amenities may also increase income through increased local demand due to in-migration or due to the increase in amenity-related consumption associated with tourism (Deller et al, 2001;Lewis, Hunt, and Plantinga, 2002;Weiler and Seidl, 2004;Monchuk et al, 2006;McGranahan and Wojan, 2007;Rappaport, 2007;McGranahan et al, 2011). This may mitigate but not reverse the income decreases in high amenities communities in spatial equilibrium.…”
Section: Testable Hypothesesmentioning
confidence: 92%
“…Florida (2002) noted the importance of high quality goods and services in attracting highly skilled labour in US cities [1] . Monchuk, et al (2006) reported that surveys focusing on quality-of-life attributes have found that recreation amenities are important to location decisions especially for high technology and information-intensive firms relying on skilled workers [10] . Specially, we predicted the following: C. Culture environment, talent growth and regional attraction Culture is the spirit headspring, which influences the growth, exploitation and using of talent.…”
Section: Hypothesesmentioning
confidence: 99%